MENINGKATAN KETERAMPILAN MENGAJAR GURU DALAM MEMBIMBING DISKUSI KELOMPOK KECIL MELALUI PENDEKATAN KOLABORATIF - ., Slamed (Jurnal Pembelajaran Prospektif, 2021)
The purpose of this study was to determine: 1). How is the process of implementing a collaborative approach in an effort to improve teacher teaching skills in guiding small group discussions; 2). Whether a collaborative approach can improve teacher teaching skills in guiding small group discussions. This type of research is School Action Research. The results of the study concluded that: 1) The process of implementing a collaborative approach was carried out in 6 stages, namely: initial conversation, observation, analysis, final conversation, final analysis and discussion. 2) A collaborative approach can improve teacher teaching skills in guiding small group discussions at SMAN 2 Sintang, SMAN 1 Sepauk and SMA Sinar Kasih Sintang. This is indicated by the average value that has increased from cycle I to cycle II. The average value of teacher teaching skills in guiding SMAN small group discussions 2 Sintang increased by 17%, at SMAN 1 Sepauk increased by 16% and at SMA Sinar Kasih Sintang increased by 15%.